Comparing developmental stability in unisexual and bisexual rock lizards of the genus Darevskia. Issue 4 (18th March 2019) - Abramjan, Andran; Frýdlová, Petra; Jančúchová‐Lásková, Jitka; Suchomelová, Petra; Landová, Eva; Yavruyan, Eduard; Frynta, Daniel
Abstract: Parthenogenetic species are usually considered to be short‐lived due to the accumulation of adverse mutations, lack of genetic variability, and inability to adapt to changing environment. If so, one may expect that the phenotype of clonal organisms may reflect such genetic and/or environmental stress. To test this hypothesis, we compared the developmental stability of bisexual and parthenogenetic lizards of the genus Darevskia . We assessed asymmetries in three meristic traits: ventral, preanal, and supratemporal scales. Our results suggest that the amount of ventral and preanal asymmetries is significantly higher in clones compared with their maternal, but not paternal, progenitor species. However, it is questionable, whether this is a consequence of clonality, as it may be considered a mild form of outbreeding depression as well. Moreover, most ventral asymmetries were found in the bisexual species Darevskia valentini . We suggest that greater differences in asymmetry levels among bisexuals may be, for instance, a consequence of the population size: the smaller the population, the higher the inbreeding and the developmental instability. On the basis of the traits examined in this study, the parthenogens do not seem to be of significantly poorer quality.